Cross-Cultural Study of Korean Leadership in Indonesia By Using Kluckhohn-Strodbeck's Framework - Suharnomo Suharnomo; Ndaru Risdanti (AFEBI Management and Business Review, 2017)
The purpose of this paper is to investigate how South Korean expatriate manager interact with Indonesian subordinates and what the difference about their culture perspective in Semarang garment enterprises and identify how the difference of culture could affect their ability to manage staff and doing their job normally. A qualitative study was conducted. Triangulation methods are used to examine the validity of research data. The result indicated South Korean manager characteristics with Kluckhohn-Strodtbeck’s dimension. There are contrast differences between South Korean manager with Indonesia employee in perception of time and space, which required adjustments in management practice for better performance results. Keywords: Expatriate Manager, Leadership, National Culture, Organizational Culture